Outcomes and impact assessment on skill courses program in community college Malaysia - Don, Yahya; Daud, Yaakob; Kasim, Abd Latif; Sakdan, Mohd Fo'ad; Omar Fauzee, Mohd Sofian (European Scientific Institute, 2014)
The Malaysian Community Colleges is an access for secondary school level to obtain knowledge and skills before they involve into the job market or pursue their education at a higher level.Community Colleges of Malaysia intend to transform into an education center of excellence in the fields of technology, business and service industries.The purpose of this working paper is to present findings studies of family income, differences income before and after enrolling in courses, distribution income during and after the course, current income distribution and type of employment, and level of self-confidence of the participants and quality of services of Community colleges in Malaysia.This study applies cross section survey method based on questionnaires that are answered by respondents.Cluster Sampling is used due to the large population. The findings of the study shows an increase in the level of self confidence, self competency of participants and increase in income after going through the programmes at Malaysian Community Colleges.Suggestions to enhance the quality of services, lecturers and ICT were also discussed towards improving qualities of service and skills-based programmes and life long learning in Malaysia for the future.